A new epi-neoverrucosane-type diterpenoid from the liverwort Pleurozia subinflata in Borneo - Takashi Kamada; Mary Lyn Johanis; Ng, Shean Yeaw; Phan, Chin Soon; Monica Suleiman; Charles S. Vairappan (2020)
New bioactive 13-epi-neoverrucosane diterpenoid, 5β-acetoxy-13-epi-neoverrucosanic acid (1) along with three known secondary metabolites, 13-epi-neoverrucosan-5β-ol (2), chelodane (3) and (E)-β-farnesene (4) were isolated from the MeOH extract of east Malaysia’s liverwort Pleurozia subinfata. The chemical structure of new compound was elucidated by the analyses of its spectroscopic data (FTIR, NMR and HR-ESI-MS). These epi-neoverrucosane-type compounds seem to be notable chemosystematic markers for P. subinfata in Borneo. Compound 3 was widespread in marine sponges however this is the frst record for 3 to be found in liverwort. These metabolites were tested for their antifungal potentials against selected fungi from the marine environment. Compound 1 exhibited efective antifungal activity against Lagenidium thermophilum.